Patient-Physician Discordance in Assessment of Adherence to Inhaled Controller Medication: a Cross-Sectional Analysis of Two Cohorts - Jácome, C (2019)
Submitted by Ana Quininha (ana.quininha@chlc.min-saude.pt) on 2019-11-12T15:26:15Z No. of bitstreams: 1 BMJ Open.pdf: 499053 bytes, checksum: 1cfa66ac8e50a4cac0b2b5d25393b57c (MD5)